Analisis Pengukuran Kinerja Keuangan Daerah Pemerintah Kabupaten Buton Selatan - Asmar, La Ode; Ridzal, Nining Asniar (Journal of Culture Accounting and Auditing, 2024)
This research aims to determine the Financial Performance of the Regional Government of South Buton Regency in terms of Financial Ratios including the Independence Ratio, Effectiveness Ratio, Regional Financial Activity Ratio, and Growth Ratio. The data used in this research is the South Buton Regency Regional Government Budget Ralization Report for 2018-2022. In this research, the method used is quantitative descriptive analysis method. Data collection methods were carried out by interviews and documentation. Based on the research results, the following conclusions were obtained: (1) The Regional Financial Independence Ratio is still very low in the instructive relationship pattern because the average is 3.91%, (2) The Effectiveness Ratio shows that the Regional Financial Performance of the South Buton Regency Regional Government is categorized as very effective because the average is 172.15%, (3) The financial activity ratio of the Regional Government of South Buton Regency shows that the majority of funds owned by the Government of South Buton Regency still prioritize operational spending with an average of 67.95% compared to average capital expenditure is 30.09%, and (4) the Growth Ratio shows that the Financial Performance of the South Buton Regency Regional Government is always fluctuating and categorized as less than good.